a)25-y²=(5-y)(5+y)
б)х²+6х+9=(х+3)²
в)4х²-4х+1=(2х-1)²
г)4у²-12у+9=(2у-3)²
д)9m²+24m+16=(3m+4)²
e)(5c-1)²-(4c-1)²=(5c-1-4c+1)(5c-1+4c-1)=c(9c-2)
а)
б)
в)
г)
д)
е)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
a)25-y²=(5-y)(5+y)
б)х²+6х+9=(х+3)²
в)4х²-4х+1=(2х-1)²
г)4у²-12у+9=(2у-3)²
д)9m²+24m+16=(3m+4)²
e)(5c-1)²-(4c-1)²=(5c-1-4c+1)(5c-1+4c-1)=c(9c-2)
Verified answer
а)![\displaystyle \tt 25-y^2=\bold{(5-y)(5+y)} \displaystyle \tt 25-y^2=\bold{(5-y)(5+y)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Ctt%2025-y%5E2%3D%5Cbold%7B%285-y%29%285%2By%29%7D)
б)![\displaystyle \tt x^2+6x+9=x^2+2\cdot x\cdot3+3^2=(x+3)^2=\bold{(x+3)(x+3)} \displaystyle \tt x^2+6x+9=x^2+2\cdot x\cdot3+3^2=(x+3)^2=\bold{(x+3)(x+3)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Ctt%20x%5E2%2B6x%2B9%3Dx%5E2%2B2%5Ccdot%20x%5Ccdot3%2B3%5E2%3D%28x%2B3%29%5E2%3D%5Cbold%7B%28x%2B3%29%28x%2B3%29%7D)
в)![\displaystyle \tt 4x^2-4x+1=(2x)^2-2\cdot 2x \cdot 1+1^2=(2x-1)^2=\bold{(2x-1)(2x-1)} \displaystyle \tt 4x^2-4x+1=(2x)^2-2\cdot 2x \cdot 1+1^2=(2x-1)^2=\bold{(2x-1)(2x-1)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Ctt%204x%5E2-4x%2B1%3D%282x%29%5E2-2%5Ccdot%202x%20%5Ccdot%201%2B1%5E2%3D%282x-1%29%5E2%3D%5Cbold%7B%282x-1%29%282x-1%29%7D)
г)![\displaystyle \tt 4y^2-12y+9=(2y)^2-2\cdot 2y \cdot3+3^2=(2y-3)^2=\bold{(2y-3)(2y-3)} \displaystyle \tt 4y^2-12y+9=(2y)^2-2\cdot 2y \cdot3+3^2=(2y-3)^2=\bold{(2y-3)(2y-3)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Ctt%204y%5E2-12y%2B9%3D%282y%29%5E2-2%5Ccdot%202y%20%5Ccdot3%2B3%5E2%3D%282y-3%29%5E2%3D%5Cbold%7B%282y-3%29%282y-3%29%7D)
д)![\displaystyle \tt 9m^2+24m+16=(3m)^2+2\cdot 3m \cdot 4+4^2=(3m+4)^2=\bold{(3m+4)(3m+4)} \displaystyle \tt 9m^2+24m+16=(3m)^2+2\cdot 3m \cdot 4+4^2=(3m+4)^2=\bold{(3m+4)(3m+4)}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Ctt%209m%5E2%2B24m%2B16%3D%283m%29%5E2%2B2%5Ccdot%203m%20%5Ccdot%204%2B4%5E2%3D%283m%2B4%29%5E2%3D%5Cbold%7B%283m%2B4%29%283m%2B4%29%7D)
е)